1990
DOI: 10.1159/000216178
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of the Low-Molecular-Weight Heparin CY 216 in the Prevention of Fatal Pulmonary Embolism and Thromboembolic Death in General Surgery

Abstract: Deep venous thrombosis is very frequent after general surgery, and its major complication, pulmonary embolism, is today the most frequent cause of postoperative death. The reduction of this cause of mortality is mainly based on its prevention rather than its therapy. This purpose was achieved by using physical and pharmacological means. During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Clinical trials have shown that LMW heparins are effective in preventing DVT following general (13)(14)(15) and orthopedic surgery (16)(17)(18) and in reducing post-operative mortality (19). Reports on the use of these agents for the treatment of established DVT are less numerous (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have shown that LMW heparins are effective in preventing DVT following general (13)(14)(15) and orthopedic surgery (16)(17)(18) and in reducing post-operative mortality (19). Reports on the use of these agents for the treatment of established DVT are less numerous (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Mientras que la introducción de tromboprofilaxis farmacológica, si ha modificado la incidencia de ETE en los pacientes quirúrgicos (18,19), no parece que el efecto haya sido similar en los pacientes "médicos" (20). Así en las series recientes de autopsia donde se objetivó tromboembolismo pulmonar, solo una cuarta parte de los pacientes tenían antecedentes quirúrgicos, dato que se mantiene también en nuestro estudio (22,5%).…”
Section: Discussionunclassified
“…Can the Multicentre Trial (MCT) 15 trial of 1975 and the Step Study Group (STEP) 16 trial of 1990 be compared? The fact that there were four times more fatal PEs in the untreated control group in the earlier trial for unknown reasons (16 of 2045 and 4 of 2247, respectively) makes one suspicious of a difference between either the designs of the two trials or a difference in clinical or technical skills over time.…”
Section: Time Between Trialsmentioning
confidence: 99%
“…In addition, the use of LMWH seems to reduce the incidence of nonfatal PEs (Table 5). In Table 5, the calculation for the placebo group was not carried out because approximately 90% of the patients of this group are from the STEP study 16 in which the endpoint was the prevention of fatal PE and thus the nonfatal PEs were not reported.…”
Section: Table 3 Record Of the Reported Pes Regardless Of Type And Qmentioning
confidence: 99%